2012
DOI: 10.1590/s0100-69162012000200007
|View full text |Cite
|
Sign up to set email alerts
|

Mudanças nas características físico-químicas de um latossolo vermelho-amarelo distrófico após a irrigação com água de reúso na cultura da alface-crespa (Lactuca sativa, L.)

Abstract: RESUMO:A utilização do efluente de esgoto tratado para poupar os corpos d´água utilizados para irrigação tem sido de grande interesse na agricultura, e o uso não regulamentado desta prática pode acarretar mudanças no comportamento físico-químico do solo. Sua prática tem sido de grande interesse em vista da redução da quantidade de água retirada dos mananciais, preservando-os. Objetivou-se, neste trabalho, a avaliação dos atributos físico-químicos de um Latossolo Vermelho--Amarelo após aplicação de água de reús… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 12 publications
(6 reference statements)
1
5
0
9
Order By: Relevance
“…Porém, pelos maiores aportes de N, P, K e menores de sódio observados na ARB, a exigência nutricional da cultura é atendida com menores doses da ARB, inclusive com 150% da exigência em K (T4), o que pode minimizar problemas de acúmulo de sódio no solo, decorrentes de aplicações sucessivas de AR. Ressalta-se que o aporte de sódio ao solo pode promover alterações em sua condição física, devido à dispersão de argila (LEAL et al, 2009;MATOS et al, 2013;VARALLO et al, 2012).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…Porém, pelos maiores aportes de N, P, K e menores de sódio observados na ARB, a exigência nutricional da cultura é atendida com menores doses da ARB, inclusive com 150% da exigência em K (T4), o que pode minimizar problemas de acúmulo de sódio no solo, decorrentes de aplicações sucessivas de AR. Ressalta-se que o aporte de sódio ao solo pode promover alterações em sua condição física, devido à dispersão de argila (LEAL et al, 2009;MATOS et al, 2013;VARALLO et al, 2012).…”
Section: Resultsunclassified
“…Esta redução no uso de adubos minerais é possível em decorrência da elevada concentração de nutrientes na AR LEAL et al, 2009;VARALLO et al, 2012), desde que a mesma seja manejada de forma criteriosa (MATOS et al, 2013).…”
Section: Introductionunclassified
“…Their inadequate destination may contribute to the increase of costs concerning water treatment headed for human consumption. According to VARALLO et al (2012), the hydric bodies are considered natural purifier of the man-generated waste. However, this very common practice is compromises the quality of the environment.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of this material for the soil in the form of fertirrigation can supply part of the nutritional needs of the crops, reduce the fertilizer costs avoid the disposal in water bodies, besides allowing better use by plants,, due to the installment of fertilization (Souza et al, 2012;Andrade Filho et al, 2013). When assessing the agricultural potential of effluent domestic sewage, Carr et al (2011) found that on average the effluent used on farms in Jordan replaces up to 75% of fertilizer needs.…”
mentioning
confidence: 99%
“…This reduction in the use of mineral fertilizers is possible due to the high concentration of nutrients in wastewater (Varallo et al, 2012), since it is handled judiciously (Matos et al, 2013). Giving this conjecture, the plants play a significant role, extracting macro and micronutrients provided by the wastewater, necessary for the growth avoiding accumulation, the consequent salinization of the soil and the contamination of surface and groundwater (Ribeiro et al, 2009).…”
mentioning
confidence: 99%